¡A leer se dijo, con papá y mamá yo puedo! Propuesta didáctica para la mediación de los padres en la iniciación lectora - Julio Chitiva, Laura Yelitza (Universidad Antonio Nariño, 2024)
This monograph emerges from the interest of linking parents to the reading initiation of their children. In this sense, the work explores the ways of their participation in Manablanca Municipal Institution, located in the municipality of Facatativa. The parents participate, basically, in processes related to coexistence and discipline, and as physical resource providers. Given this situation, a didactic proposal is developed in order to seek mediation of parents in the reading initiation of their children, on the basis of the encounter among children's literature, school and parents.